Mapping of national literacy public policies in Brazil - Araujo, Viviane Patricia Colloca (Educação, Escola & Sociedade, 2024)
This documentary research sought to map the national literacy public policies in Brazil, from 1985 to 2022. Reflecting on public policies implies analyzing the historical, political and economic context in which these policies were elaborated. Globalization and neoliberalism are the background of this context that begins to intensify in the 1980s. Thus, it is this scenario based on a neoliberal policy and economic and cultural globalization that important meetings were held to implement a world education agenda. The results of this research demonstrate that we still lack literacy public policies that bring effective results to overcoming illiteracy among young people and adults and a strengthening of pedagogical practices for children's literacy that are really effective in the success of the process of learning to read and write.